FULL-TIME EDUCATION:: PERCEPTIONS OF TEACHING THROUGH A SOCIO-ENVIRONMENTAL PROJECT (Interdisciplinary Studies Journal, 2026)
Basic education professionals working in Environmental Education (EE) have the mission of promoting issues related to the human-nature relationship over time and awakening the pleasure of caring for nature. Given the above, this work aimed to present and analyze the possibilities of pedagogical practices that have been and can be developed in disciplines that include EE in full-time elementary schools and other modalities, based on the experiences acquired at the Tancredo Neves Municipal School, located in the city of Cáceres, Mato Grosso. This work was based on experience reports of participatory methodologies developed within the area of ​​Science and Technology, Sustainability, Prevention, and Citizenship as a Curricular Component in the diversified section, conducted from May to November 2024, using a qualitative approach. The approach proposed teaching EE through experiences aimed at raising students' awareness of socio-environmental issues. The conclusion is that Full-Time Education supports the development of practical Environmental Education teaching activities. The extended time facilitates the involvement of other disciplines, making interdisciplinarity a reality through support for the development of socio-environmental projects.
Keywords: Full-Time Education; Environmental Education; Environmental Didactics